1992
DOI: 10.1161/01.res.70.3.508
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in membrane Ca2+ and K+ currents in fetal, neonatal, and adult rabbit ventricular myocytes.

Abstract: Whole-cell calcium current (ICa) and inwardly rectifying potassium current (IK1) were studied in 21-day fetal, 28-day fetal (total gestation, 31 days), 2-5-day neonatal, and adult rabbit ventricular myocytes isolated by enzymatic dissociation. Whole-cell peak ICa and IK1 at -100 mV increased significantly after birth. Cell size approximated from cell membrane capacitance also increased with age, with the most significant increase occurring after birth. When normalized to cell surface area, peak ICa density inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
2
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 30 publications
10
56
2
1
Order By: Relevance
“…Relative to other inward rectifier K ϩ channels, K ATP channels are expressed at high density during early developmental stages and therefore may have an important physiologic role during this period (1-3). However, K ATP channel activity is strongly up-regulated during postnatal development in parallel to that of the classical "inward rectifier current" I K1 (52). Our data demonstrating up-regulation of individual K ATP channel subunits during development are consistent with this increased K ATP channel current during perinatal development.…”
supporting
confidence: 80%
“…Relative to other inward rectifier K ϩ channels, K ATP channels are expressed at high density during early developmental stages and therefore may have an important physiologic role during this period (1-3). However, K ATP channel activity is strongly up-regulated during postnatal development in parallel to that of the classical "inward rectifier current" I K1 (52). Our data demonstrating up-regulation of individual K ATP channel subunits during development are consistent with this increased K ATP channel current during perinatal development.…”
supporting
confidence: 80%
“…5). Systolic [Ca 2ϩ ] i , C m , and I Ca density were larger in adult than in 3-wk-old rabbit ventricular myocytes, in agreement with previous reports (37)(38)(39). In an earlier study (2), we found larger and faster sarcomere shortening in the adult myocyte, consistent with its higher systolic [Ca 2ϩ ] i .…”
Section: Discussionsupporting
confidence: 92%
“…The contacted T cells could be distinguished from L cells under a microscope by their small size. The membrane capacitance was measured using a method described by Huynh and colleagues (26) and showed no difference between control and peptide-stimulated groups (membrane capacitance, 0.81 Ϯ 0.03, and 0.89 Ϯ 0.05 F/cm 2 , respectively). To record the outward currents, IS contained a K ϩ -rich solution as described above.…”
Section: Electrophysiologymentioning
confidence: 99%